Quality of handover in a pediatric postanesthesia care unit1. Issue 7 (2nd April 2015) - Piekarski, Florian; Kaufmann, Jost; Laschat, Michael; Böhmer, Andreas; Engelhardt, Thomas; Wappler, Frank; Kurth, Dean
Summary Background The quality of anesthetic handovers to postanesthesia care units (PACU) is known to be poor in adults, and only very limited reports are available regarding the quality of handovers in pediatric anesthesia. In particular, it is not known which and in what quality information is communicated. This current study investigated, therefore, the presence of any handover component as well as its consistency in a pediatric postanesthesia care unit. Methods This prospective observational study evaluated postoperative anesthetic handovers to a pediatric PACU using a detailed checklist, comprising 55 possible items. The main outcome measure was the proportion of information verbally transmitted in relation to the written documentation within the anesthesia record. Results Four hundred and forty‐three handovers were observed with two handovers excluded due to missing data. Type of surgery (93% [95% CI 91–95]) and any intra‐operative regional anesthesia (89% [95% CI 85–94]) were most frequently communicated. Items such as ASA‐PS (3% [95% CI 2–5]) and fluid management (4% of cases [95% CI 2–6]) were rarely handed over. Eleven of the 55 items contained within the checklist were communicated in more than 70% of patients. Conclusions The observed handovers to PACU staff were incomplete and missing important information. However, omission of essential information potentially compromises patient safety. A standardized universal mandatory handover protocol following pediatric anesthesia is required.